Electrical, thermal and rheological properties of low-density polyethylene/ethylene vinyl acetate/graphene-like composite. (15th November 2019) - Azizi, Sohrab; Ouellet-Plamondon, Claudiane M.; Nguyen-Tri, Phuong; Fréchette, Michel; David, Eric
Abstract: Composites of low-density polyethylene (LDPE), ethylene vinyl acetate (EVA), and a graphene-like material were explored for their electrical properties for use in high-volume low-cost conductive applications. A graphene-like material, obtained from hybrid clay-sucrose carbonization, was investigated as an alternative filler with advantages over conventional graphene technology. The electrical properties of the composites as synthesized by the solvent–casting technique were studied using broadband dielectric spectroscopy. The percolation threshold was identified for both as synthesized and annealed composite samples. Due to charge transport and electrode polarization, the sub-percolating composites exhibited low frequency dispersion particularly at elevated temperatures. Composites of LDPE/EVA/graphene-like above the percolation threshold exhibited a higher rheological storage modulus and thermal stability which indicates an alignment between the electrical, thermal and rheological properties. Graphical abstract: Image 1 Highlights: Investigation of electrical and thermal conductivity of LDPE/EVA/graphene-like. Electrical percolation threshold was found at 17 wt% graphene-like made of clay and pyrolysed sugar. Annealing featured higher electrical conductivity.